IMPACT OF THE AGRICULTURAL CREDIT GUARANTEE SCHEME FUND ON AGRICULTURAL PRODUCTIVITY IN NIGERIA 1981-2020 - Jam, Felix A.; Tsegba, Prof. I. N.; Aondoakaa, Dr. E. K. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study ascertains the impact of the Agricultural Credit Guarantee Scheme Fund on Agricultural Productivity in Nigeria 1981-2020. The ex-post facto research design was adopted for the study. Secondary data obtained from the Central Bank of Nigeria Annual Statistical Bulletin was used for the study. Jarque Bera test statistics was used to check for data normality while the Augmented Dickey Fuller test (ADF) was used to check the stationarity of the data. Johansen co-integration and error correction model was used to estimate the nexus that exists between the variables of the study. Findings from the study revealed that in the longrun, volume of funding to crop sector (FCP) has a positive effect on the output of crops and the effect is statistically significant.  Volume of funding to livestock (FCP) is positively signed and in line with a priori expectation. Volume of funding to fishery (FFS) has positive effect on output of fishery within the period under study and this effect is in line with a priori expectation. Finally, volume of funding to forestry (FFT) is positively signed and in line with a priori expectation. The researcher concluded that quality credit to the agricultural sector is very important in both long and shortrun as agriculture plays a vital role in the life of people especially in developing countries such as Nigeria. It was recommended among others that more funding be dedicated by government to improve productivity while policy geared towards improving funding in the shortrun should be aggressively pursued by the government so as to achieve an equilibrium of positive effect of funding in both the long and shortrun period for the four sectors examined.